Correlação entre intensidade da dor, incapacidade funcional e qualidade de vida em idosos com dor lombar crônica não específica - SANTOS, Gyselle Thatiane Leão dos (2021)
Objective: To analyze the correlation between pain intensity, functional disability and quality of life in the elderly with chronic non-specific low back pain. Method: This is a cross sectional and analytical study. Thirty-five responsible elderly people with chronic non specific low back pain underwent pain assessment (Pain Numerical Rating Scale - NRS), functional disability (Roland Morris) and quality of life (SF-36). Result: Sample composed of 35 participants, with an average age of 71.2 years (± 1.1). The results are statistically. Between Pain Intensity and functional disability (rho =, 363), but not for pain intensity and Pain time, Functional Capacity and Quality of Life. Conclusion: The results of this study indicate that there is an association between pain intensity and functional disability in the elderly with chronic low back pain. This information must be taken into account by health professionals in the therapeutic planning of this population.